Peran Strategis Supervisi Pendidikan dalam Mewujudkan Siswa Madrasah Ibtidaiyah yang Berkarakter - Ashshiddiqi, Muahammad Hasbie; Hsb, Khusyairi Ahmad Hsb; Umaiyah, Siti (Prodi PGMI STIT Al-Ittihadiyah Labuhanbatu Utara, 2025)
This research is motivated by the importance of educational supervision as a strategic instrument in realizing students with character in Islamic elementary schools. A common phenomenon shows that supervision practices in Islamic elementary schools are often administratively oriented, not fully directed at fostering the moral, spiritual, and professionalism of teachers, which have implications for student character formation. Therefore, this study aims to analyze in depth the strategic role of educational supervision in shaping student character through a theoretical approach and the integration of Islamic values. The method used is library research with a qualitative-descriptive approach. Data were obtained from various scientific sources such as books, journals, previous research results, and relevant educational policies. Data analysis was conducted using content analysis and theoretical comparative techniques to find the relationship between the concept of modern educational supervision and the principles of supervision from an Islamic perspective. The research results show that educational supervision based on Islamic values ​​such as muraqabah, ihsan, and amanah plays a crucial role in creating learning that instills character values ​​in students. Collaborative and reflective supervision has been shown to enhance teacher professionalism while simultaneously building a madrasa ecosystem oriented toward moral and spiritual values. The implications of this research emphasize the need to transform the paradigm of educational supervision in madrasas into a continuous development process that integrates managerial and spiritual aspects to produce a generation that is knowledgeable, faithful, and virtuous.